2022
DOI: 10.3390/ph15040473
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 Receptor Involvement in the Actions of CBD on Anxiety and Coping Behaviors in Mice

Abstract: The anxiolytic and antidepressant properties of cannabidiol (CBD) have been evaluated in several studies. However, the molecular mechanisms involved in these actions remain unclear. A total of 130 male mice were used. CBD’s ability to modulate emotional disturbances (anxiety and depressive-like behaviors) was evaluated at different doses in wild-type (CD1; 10, 20 and 30 mg/kg; i.p.) and knockout (CB1KO, CB2KO; GPR55KO; 20 mg/kg) mice. Moreover, CBD effects (20 mg/kg; i.p.) were evaluated in mice previously tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…The third major limitation of this preliminary study is that the mechanism of action of CBD to enhance the social behavior of BTBR mice was not elucidated. CBD has more than 65 potential therapeutic targets, and comprehensive studies to discover CBDs role in shaping behaviors through them are just beginning to unfold ( 1 , 39 ). Strengths of this study include the use of multiple mouse models of ASD, a variety of behavioral tests, and measurement by mass spectrometry of serum and brain homogenate CBD and our attempt to also measure the metabolite levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third major limitation of this preliminary study is that the mechanism of action of CBD to enhance the social behavior of BTBR mice was not elucidated. CBD has more than 65 potential therapeutic targets, and comprehensive studies to discover CBDs role in shaping behaviors through them are just beginning to unfold ( 1 , 39 ). Strengths of this study include the use of multiple mouse models of ASD, a variety of behavioral tests, and measurement by mass spectrometry of serum and brain homogenate CBD and our attempt to also measure the metabolite levels.…”
Section: Discussionmentioning
confidence: 99%
“…CBD has many different pharmacological effects, and potential physiological mediators ( 1 , 39 ). Based on previously established affinities, CBD administered to mice at 10 mg/kg is unlikely to bind to and compete with CB 1 or CB 2 receptors directly ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed mechanism is by the indirect potentiation of AEA transmission since CBD can inhibit the FAAH enzyme [ 155 ] ( Figure 5 ). This could be related to a recent study that demonstrated that CB 1 R (but not CB 2 R or GPR55-KO mice models) is relevant in modulating the anxiolytic actions of CBD using knockout mice for these receptors [ 158 ]. It is possible that these mechanisms and other ones can be acting in conjunction, since CBD can interact with other receptors involved in the regulation of anxiety such as GABA A R.…”
Section: Therapeutic Evidence Involving Cbdmentioning
confidence: 94%
“…Measures to improve welfare assistance and clinical status as well as endpoint criteria were established to minimize suffering and ensure animal welfare. CBD dosing was chosen based on previous experience using CBD derivatives for treating fibrosis ( Del Rio et al, 2018 ) and literature reporting pharmacological effects of CBD in vivo ( Rajesh et al, 2010 ; Cheng et al, 2014 ; Austrich-Olivares et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%